Development and validation of a LC-MS method for the quantification of microcystins in fish for their monitoring in environmental and food context - Camille Van Camp; Wannes Hugo R. Van Hassel; Jeroen Van Wichelen; Julien Masquelier (Journal of Agriculture and Food Research)
Cyanobacterial blooms in aquatic ecosystems can result in the accumulation of cyanotoxins in other organisms. Fish can potentially accumulate large amounts of cyanotoxins through their direct interaction with contaminated water and the ingestion of cyanobacterial cells. As a human food source, this can result in a potential health risk. Investigating and monitoring this risk requires analytical methods sufficiently robust to be suitable for different fish species. This study, therefore, aimed to optimize and validate an UHPLC-MS/MS method for the quantification of eight microcystin congeners and nodularin in five different fish species. The limits of detection and quantification were 1 and 3 μg kg−1, respectively. The linearity of the method was very good, with calculated R2 values above 0.99. The mean recovery of the method was within the acceptable range of 70.0%–120.0 %, the repeatability was not higher than 12.6 %, and the highest intra-laboratory reproducibility was 18.7 %. The estimated range for the expanded measurement uncertainty was between 29 % and 58 %. Moreover, multiple fish from Flemish waters were analyzed to show the method's applicability. Multiple microcystin congeners were detected (up to 88.3 μg kg−1 sum of analyzed microcystins) in the liver and viscera of perch and sander. Small amounts of MC-LR and MC-YR (up to 6.1 μg kg−1) were also detected in perch muscle tissue.